Evaluation of subconjunctival liposomal steroids for the treatment of experimental uveitis - Wong, Chee Wai (2018)
Non-infectious anterior uveitis (AU) is a potentially sight threatening inflammatory condition. The current gold standard for treatment is topical steroids, but low ocular bioavailability and compliance issues with the intensive dosing regimen limit the efficacy of this treatment. Liposomes as a drug delivery system may help to overcome these problems. We studied the efficacy of a PEG-liposomal formulation of liposomal steroids, administered as a single subconjunctival dose, in the treatment of experimental uveitis in rabbit eyes. Rabbits that received subconjunctival liposomal triamcinolone acetonide phosphate (LTAP) or liposomal prednisolone phosphate (LPP) had significantly lower mean inflammatory scores than untreated controls on Day 4 after induction of uveitis (LPP vs controls, p=0.049) and 8 (LPP vs controls, p=0.007; LTAP vs controls, p=0.019), and lower scores than rabbits given topical PredForte1% 4 times a day on Day 8 (p=0.03). After antigen rechallenge, the subconjunctival liposomal steroid groups continued to have greater suppression of inflammation than untreated controls on Day 11 (p=0.02). Localization of liposomes in inflamed ocular tissue was confirmed by histology and immunostaining, and persisted in the eye for at least one month. Our study demonstrates that a single subconjunctival injection of liposomal steroids induces effective and sustained anti-inflammatory action.